On the Role of Cannabinoid CB1- and μ-Opioid Receptors in Motor Impulsivity - Wiskerke, Joost; Van Mourik, Yvar; Schetters, Dustin; Schoffelmeer, Anton N.; Pattij, Tommy (Frontiers in Pharmacology, 2012)
Previous studies using a rat 5-choice serial reaction time task have established a critical role for dopamine D2 receptors in regulating increments in motor impulsivity induced by acute administration of the psychostimulant drugs amphetamine and nicotine. Here we investigated whether cannabinoid CB1 and/or μ-opioid receptors are involved in nicotine-induced impulsivity, given recent findings indicating that both receptor systems mediate amphetamine-induced motor impulsivity. Results showed that the cannabinoid CB1 receptor antagonist SR141716A, but not the opioid receptor antagonist naloxone, reduced nicotine-induced premature responding, indicating that nicotine-induced motor impulsivity is cannabinoid, but not opioid receptor-dependent. In contrast, SR141716A did not affect impulsivity following a challenge with the dopamine transporter inhibitor GBR 12909, a form of drug-induced impulsivity that was previously found to be dependent on μ-opioid receptor activation. Together, these data are consistent with the idea that the endogenous cannabinoid, dopamine, and opioid systems each play important, but distinct roles in regulating (drug-induced) motor impulsivity. The rather complex interplay between these neurotransmitter systems modulating impulsivity will be discussed in terms of the differential involvement of mesocortical and mesolimbic neurocircuitry.